2013
DOI: 10.4311/2011es0262
|View full text |Cite
|
Sign up to set email alerts
|

Flow Characterization in the Santee Cave System in the Chapel Branch Creek Watershed, Upper Coastal Plain of South Carolina, USA

Abstract: Karst watersheds possess both diffuse and conduit flow and varying degrees of connectivity between surface and groundwater over spatial scales that result in complex hydrology and contaminant transport processes. The flow regime and surfacegroundwater connection must be properly identified and characterized to improve management in karst watersheds with impaired water bodies, such as the Chapel Branch Creek (CBC), South Carolina watershed, which has a long-term sampling station presently listed on an EPA 303(d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…This is particularly important in arid and semi-arid countries as the demand for water is ever increasing for agriculture, industry and community water supplies (WWRD, 2015). Karst aquifers possess both diffuse and conduit flow and varying degrees of connectivity between surface and groundwater over spatial scales that results in complex hydrology (Edwards et al, 2013). The surface-groundwater connection and flow regime must be properly identified and characterized to improve management of karst aquifers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important in arid and semi-arid countries as the demand for water is ever increasing for agriculture, industry and community water supplies (WWRD, 2015). Karst aquifers possess both diffuse and conduit flow and varying degrees of connectivity between surface and groundwater over spatial scales that results in complex hydrology (Edwards et al, 2013). The surface-groundwater connection and flow regime must be properly identified and characterized to improve management of karst aquifers.…”
Section: Introductionmentioning
confidence: 99%
“…Geochemical and isotopic data have been used in numerous studies in different karst regions to characterize the flow in carbonate aquifers and degree of surface-groundwater connections (Edwards et al, 2013). Knierim et al (2015) show that stable isotope analyses are valuable in karst settings.…”
Section: Introductionmentioning
confidence: 99%
“…Both the monitoring and modeling approaches provided a better understanding of the hydrologic and nutrient cycling and transport (flow pathways) processes on the watershed of interest. Potential effects of karst features and interactions with Lake Marion level on hydrology and potential flow paths of the CBC watershed have been recently discussed by [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in the Opequon Creek watershed study, [26] found that a SWAT-Karst model that used the HRU to represent sinkholes had a more notable impact in the watershed hydrology than SWAT-B&B using a pond to represent sinkholes; the author reported that the SWAT-karst and the SWAT-B&B version performed better than the SWAT alone for predicting streamflow in a karst-influenced watershed. Most recently, [27] used the SWAT model to simulate the monthly streamflow pattern and dynamics of the karst affected CBC watershed tributaries and its embayment adjacent to Lake Marion, water levels of which dynamically influence the hydrology and water quality of the CBC system [8,9]. Results demonstrated the substantial influence on the water balance of the karst features with conduit and diffuse flow as an explanation [9] for the missing upstream flows appearing via subsurface conveyance to the downstream cave spring [8] providing a more accurate simulation at the embayment outlet [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation